ANALYSIS OF THE EFFECT OF OPEN UNEMPLOYMENT RATE AND MINIMUM WAGE ON POVERTY LEVEL IN INDONESIA - Karim, M.; Antoni, Syafrul; Oktarina, Karlini (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This study aims to analyze the effect of open unemployment and minimum wages on poverty levels in Indonesia. The study employs secondary data with a sample of 34 provinces in Indonesia. The sample was determined using the simple random sampling technique. Data were analyzed using multiple linear regression. Data quality tests included validity testing using Pearson correlation and reliability testing using Cronbach’s Alpha. Hypothesis testing was conducted using the coefficient of determination (Adjusted R²), F-test, and t-test. The results indicate that open unemployment has a significant effect on poverty levels in Indonesia. Meanwhile, the minimum wage does not have a significant effect on poverty levels. Simultaneously, open unemployment and minimum wages have a significant effect on poverty levels in Indonesia. The findings of this study are expected to provide policy-relevant insights for the government in formulating employment and poverty alleviation policies.